2014
DOI: 10.1039/c4ta04338c
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of nanoscale morphology in single and binary metal oxide microparticles during reduction and oxidation processes

Abstract: Metal oxide composites are enabling materials for many energy conversion systems such as chemical looping and photocatalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 36 publications
1
43
0
Order By: Relevance
“…Subsequently, the NiFe alloys were reoxidized by O 2 to form NiFe 2 O 4 . Due to differences in the oxidation and ion diffusion rates of Ni and Fe, uniform NiFe microparticles are transformed into particles with a NiO‐rich core and a Fe 2 O 3 ‐rich shell during oxidation . So, the phase segregation of NiFe 2 O 4 gradually occurred with the increase of redox cycles.Reduction: NiFe2normalO4+ normalH2Ni + Fe3normalO4+ normalH2O NiFe + normalH2O Oxidation: NiFe + normalO2NiFe2normalO4 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, the NiFe alloys were reoxidized by O 2 to form NiFe 2 O 4 . Due to differences in the oxidation and ion diffusion rates of Ni and Fe, uniform NiFe microparticles are transformed into particles with a NiO‐rich core and a Fe 2 O 3 ‐rich shell during oxidation . So, the phase segregation of NiFe 2 O 4 gradually occurred with the increase of redox cycles.Reduction: NiFe2normalO4+ normalH2Ni + Fe3normalO4+ normalH2O NiFe + normalH2O Oxidation: NiFe + normalO2NiFe2normalO4 …”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the surface Fe atomic ratio of fresh and spent NiFe 2 O 4 OCs based on the EDS‐mapping results in Figure and . Due to no Ni migration in the redox reactions, atomic ratio of Fe/(Fe + Ni) was used to quantify the Fe concentration changes on the surface of NiFe 2 O 4 OCs. Compared with the EDX‐mapping images in Figure , the surface concentration of Ni, Ce, and Zr decreased significantly for CeZrO 2 –NiFe 2 O 4 and ZrO 2 –NiFe 2 O 4 after ten redox cycles, as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9, probably due to the iron migration onto the surface of oxygen carriers. Qin et al (2014) analyzed the core-shell structure formations of FeNi microparticles during the cyclic oxidation-reduction reaction, and reported that the outward iron ions diffusion was faster than the inward oxygen diffusion in iron oxide. Hence, the preliminarily simplified mechanism for iron cations diffusion of FeAl320-S10 and FeTi320-S0 pellets during reduction and oxidation operations are demonstrated as Fig.…”
Section: Resultsmentioning
confidence: 99%